2015
DOI: 10.1155/2015/435947
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Autoimmune Thyroid Disease in Alopecia Areata and Vitiligo Patients

Abstract: Aim. Many studies demonstrated that alopecia areata (AA) and vitiligo are commonly associated with autoimmune thyroid diseases. We aimed to investigate the frequency of thyroid dysfunctions and autoimmunity related with vitiligo and AA. Material and Methods. 200 patients, 92 AA and 108 vitiligo diagnosed, were surveyed retrospectively. The control population was in reference range and from Konya, central Anatolian region of Turkey. Thyroid function tests (free T3, free T4, and TSH) and serum thyroid autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 19 publications
1
27
2
3
Order By: Relevance
“…However, Gulcan Saylam Kurtipek, et al, found high levels of anti-TPO in 16 (14.8%) and anti-TG in 9 (8.3%) out of 108 vitiligo patients, these rates are lower than our study [16]. In addition, previous studies reported a significantly increased prevalence of vitiligo in patients with autoimmune thyroid disease compared to patients with non-autoimmune thyroid disease [10,16].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, Gulcan Saylam Kurtipek, et al, found high levels of anti-TPO in 16 (14.8%) and anti-TG in 9 (8.3%) out of 108 vitiligo patients, these rates are lower than our study [16]. In addition, previous studies reported a significantly increased prevalence of vitiligo in patients with autoimmune thyroid disease compared to patients with non-autoimmune thyroid disease [10,16].…”
Section: Discussioncontrasting
confidence: 74%
“…In addition, previous studies reported a significantly increased prevalence of vitiligo in patients with autoimmune thyroid disease compared to patients with non-autoimmune thyroid disease [10,16].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, results vary among studies. Positive thyroglobulin antibodies were found in 22–46% of patients with AA and positive thyroid peroxidase antibodies were found in 9–48% of patients with AA . Abnormal thyroid function tests were found in 8.9–27% of patients with AA .…”
Section: Discussionmentioning
confidence: 96%
“…Several other studies document higher frequencies of AITD in women . Conversely, another study found the association between overt thyroid disease and vitiligo to be stronger in males compared to females, while others found no association between gender and AITD or between gender and anti‐TPO levels …”
Section: Specific Autoimmune Comorbiditiesmentioning
confidence: 95%
“…Alopecia areata is an autoimmune disease that is characterized by patchy or total hair loss of the scalp hair and sometimes universal loss of all body hair . A sizable proportion of vitiligo patients have simultaneous alopecia areata.…”
Section: Specific Autoimmune Comorbiditiesmentioning
confidence: 99%